Effects of chronic exposure to benzalkonium chloride in Oncorhynchus mykiss: cholinergic neurotoxicity, oxidative stress, peroxidative damage and genotoxicity - Antunes, S. C (2022)
Benzalkonium chloride (BAC) is one of the most used conservatives in pharmaceutical preparations. However, its use is limited to a small set of external use formulations, due to its high toxicity. Benzalkonium chloride effects are related to the potential exertion of deleterious effects, mediated via oxidative stress and through interaction with membrane enzymes, leading to cellular damage. To address the ecotoxicity of this specific compound rainbow trouts were chronically exposed to BAC at environmental relevant concentrations (ranging from 0.100 to 1.050mg/L), and the biological response of cholinergic neurotoxicity, modulation of the antioxidant defense, phase II metabolism, lipid peroxidation and genotoxicity was studied. The obtained results showed a dual pattern of antioxidant response, with significant alterations in catalase activity (starting at 0.180mg/L), and lipid peroxidation, for intermediate (0.180 and 0.324mg/L) concentrations. No significant alterations occurred for glutathione-S-transferases activity. An unexpected increased of the acetylcholinesterase activity was also recorded for the individuals exposed to higher concentrations of BAC (starting at 0.180mg/L). Furthermore, exposure to BAC resulted in the establishment of genotoxic alterations, observable (for the specific case of the comet assay results) for all tested BAC concentrations. However, and considering that the oxidative response was not devisable, other mechanisms may be involved in the genotoxic effects reported here.